Personal view: hormones and depression in women. (February 2015) - Studd, J.
Abstract Depression is more common in women, occurring at times of hormonal fluctuations as premenstrual depression, postnatal depression and perimenopausal depression. These are all related to changes in hormone levels and constitute the diagnosis of reproductive depression. There is a risk that severe premenstrual depression can be misdiagnosed as bipolar disorder and that women will be started on inappropriate antidepressants or mood-stabilizing therapy. The most effective treatment for severe premenstrual syndrome is by suppression of ovulation and suppression of the cyclical hormonal changes by transdermal estrogens or by GnRH analogs. Postnatal depression is more common in women with a history of premenstrual depression and also responds to transdermal estrogens. Transdermal testosterone gel can be also used in women who suffer loss of energy and loss of libido which may be due to the inappropriate prescription of antidepressants. There is also a role for the Mirena IUS and laparoscopic hysterectomy and oophorectomy in women who are progestogen-intolerant. The hormonal causation of certain common types of depression in women and the successful treatment by estrogens should be understood by psychiatrists and gynecologists.